Precedent Phenomena as a Way of Transmitting the Author's Intention - Nikiforova, E.Sh.; Simanchuk, Ye.A. (KU Publ., 2021)
The article discusses a wide range of precedent phenomena in the texts on politics and economics within English media discourse. The author emphasizes the fact that precedent texts, being one of the ways of reflecting the peculiarities of a linguistic culture, are exploited by compilers of media texts in order to activate and explicate additional meanings and connotations. The overwhelming majority of the reviewed texts is characterized by the use of the category of precedence as a way to express the author's intention through referential and evaluative functions, when, through a precedent phenomenon, the journalist encodes his assessment in relation to the events described. In addition, precedent texts often perform a password function that saves linguistic resources and, thus, the author's intention is expressed in a more concise form, making a reference to the mental-verbal base of the audience.
Прецеденттік құбылыстар автордың ойын жеткізудің тəсілі ретінде
Прецедентные феномены как способ передачи авторского замысла
Keywords: precedent phenomenon; media discourse; author's intention; linguistic culture; referential function; password function; evaluative function